Implementing Biodrying Method for Waste Processing in Salatiga City - Hardyanti, Nurandani; Zaman, Badrus; Bagaskhara, Rezza Anferditya; Hasfiawan, Harsya Giras (Universitas Diponegoro, 2024)
Waste processing in Salatiga City could have been more optimal. It can be seen from the data from the Salatiga City Environment Service that the waste processing facility in the form of an active waste processing site with reduce-reuse-recycle is only one out of seven registered units. This has the potential to cause accumulation at the final processing site. Therefore, it is necessary to develop an effective waste processing facility. Planning for waste processing using the biodrying method can effectively process waste that produces products in the form of Refuse Derived Fuel (RDF)[1] [Ma2] . Planning for waste processing is carried out until 2032 in two service areas: Service area 1 (Argomulyo District and Tingkir District) and service area 2 (Sidorejo District and Sidomukti District). The amount of waste generated by service area 1 reaches 49.33 tons/day and 522.67 m3/day, while service area 2 reaches 49.62 tons/day and 414.01 m3/day. Planning for waste processing using the drying method includes picking bay units, shredding, drying, screening, and loading RDF.[3] [Ma4] RDFs potential in 2032 as a result of waste processing in service area 1 is 11159.03 tons/year with sales of Rp. 7,270,755,009 / year and in service area 2 it is 10,471.09 tons / year with sales of Rp. 6,822,524,206 / year